Soil Structure under Forest and Pasture Land-Uses Affecting Compressive Behavior and Air Permeability in a Subtropical Soil - Suzuki, Luis Eduardo Akiyoshi Sanches; Reinert, Dalvan José; Secco, Deonir; Fenner, Paulo Torres [UNESP]; Reichert, José Miguel (MDPI, 2022)
Machinery traffic and animal trampling can deform the soil and, consequently, impair soil pore functioning. This study aimed to evaluate how soil structure affects the compressibility, physical properties and air permeability of a Typic Paleudalf under forest, pasture and eucalyptus. Soil samples with preserved structure were used to determine soil physical (bulk density, porosity, degree of water saturation at 33 kPa-tension, air permeability) and mechanical properties (soil deformation, precompression stress, compressibility index). After these evaluations, each soil sample was fragmented, sieved, and the metal rings filled with structureless soil, and underwent the same determinations as the samples with preserved structure. For loads greater than the precompression stress (load greater than 200 kPa), soil with non-preserved structure had the largest deformation. An increase in bulk density decreased macropores linearly (R2 = 0.77 and 0.87, respectively, to preserved and non-preserved soil structure) and air flow exponentially. The soil with preserved structure was less susceptible to further compaction. Air flow was greatest in soils with lower bulk density, microporosity and water saturation degree, and a high volume of macropores. Soil structure (preserved and non-preserved) had more significative differences in microporosity, compressibility index, soil deformation, and bulk density at the end of the compression test.
Keywords: compressibility; precompression stress; soil compaction; soil permeability